BALANCING EFFICIENCY AND HUMANITY IN THE ADOPTION OF ARTIFICIAL INTELLIGENCE AMONG INDONESIAN PRIMARY SCHOOL TEACHERS - Hamdan Husein Batubara (PD PGMI se Indonesia, 2026)
The potential of Artificial Intelligence (AI) in streamlining teachers' tasks is often unattainable for some primary school teachers in developing countries due to the wide digital divide, ethical issues, and AI hallucinations. This study aims to explore the views and strategies of primary school teachers in Indonesia for balancing the drive to improve work efficiency with the need to uphold pedagogical ethics and protect student safety. Through a reflective questionnaire, this descriptive-exploratory qualitative study collected in-depth narratives from 100 primary school teachers in Indonesia. Open-ended answers were analyzed to understand their views and life experiences. The results of this study reveal that teachers have carefully used AI as a tool to speed up the completion of administrative tasks and design creative learning scenarios and media, while maintaining students' privacy and independence of thinking. Although the use of AI is incompatible with inadequate infrastructure, large skills gaps, algorithmic bias, and less supportive regulations and policies, teachers demonstrate their active role as ethical and reflective agents who constantly cross-validate AI results rigorously and continue to learn how to use AI appropriately. These findings suggest that the use of AI among primary school teachers requires not only technical training but also policies that foster ethical and critical awareness in the use of technology, thereby reinforcing human values.